Aging and Elderly Care Practice in Japan: Main Issues, Policy and Program Perspective; What Lessons can be Learned from Japanese Experiences? - Raikhola, Pushkar Singh; Kuroki, Yasuhiro (Dhaulagiri Journal of Sociology and Anthropology, 2010)
This article presents an overview of the main issues, policies and programs related to aging and elderly care practice of Japan based on the available published evidence to date. The Japanese enjoy the world's longest and healthiest lives. This fortunate situation, however, is also causing concern. The rate of population aging in Japan is much greater than that in other developed countries. In Japan, the nuclear family, female employment, decreased fertility rate and changing patterns of family roles have combined to make it more difficult or less desirable to provide that care informally and there are greatly increased demands for community and institutional care. The aging process of Japan not only increased the ratio of the elderly in the population but also accompanied a fundamental change in family and community. Therefore, the various systems which are affected by these changes, such as pensions, medical care and long term care, need to be rebuilt. The aging issue requires a long term commitment with enough foresight; policies must be created as soon as possible with consideration for cultural and social conditions specific to each country and each city. I think the care of the elderly therefore involves a holistic combination of health care, socio-economic care and the provision of suitable environment. In Japan the Long Term Care Insurance Plan and the New Gold Plan alongside other policies and programs are directed towards the care and welfare of elderly people. These policies and programs are actually imitable for countries like Nepal, where are no any substantial policies and programs for caring the elderly. So that we can learn various experiences of coping aging and elderly problem from Japan both in policy and program level. However, Nepal should develop its own policies and programs based on its own cultural traditions, economic capacity and social transitions in the society. Key Words: Aging; elderly care; fertility; policy; programs; Japan; Nepal. DOI: 10.3126/dsaj.v3i0.2781 Dhaulagiri Journal of Sociology and Anthropology Vol.3 2009 41-82